The influence of ceramic re-pressing on surface properties, bond strength, and color stability of leucite ceramic - Abu-Izze, Fernanda O. [UNESP]; Dal Piva, Amanda M.O. [UNESP]; Bottino, Marco A. [UNESP]; Valandro, Luiz Felipe; de Melo, Renata Marques [UNESP] (My University, 2018)
Purpose: To evaluate the influence of recycling a pressed ceramic material on surface properties, color stability and bond strength to composite cement. Materials and Methods: Forty-eight (48) ingots from a heat-pressed ceramic (PM9, Vita Zahnfabrik) were fabricated through the lost-wax technique and then polished with SiC sandpaper to standardize the dimensions (diameter: 12 mm; length: 4 mm). Leftover material from processing the pressed groups was retrieved and used to repeat heat pressing for the re-pressed groups. The ingots were randomly divided into 3 groups according to the number of injections - one, two, or three times. Ra, Rz, and RSm surface roughness parameters were evaluated through a contact rugosimeter. Topography was analyzed using SEM and the chemical constituents using EDS (energy dispersive spectroscopy). Color stability was evaluated according to CIE-Lab parameters to determine color variation (ΔE). Composite ingots with the same dimensions were cemented over each ceramic, then this set was cut into sticks with a 1-mm2 cross-sectional area. Half of the sticks were submitted to microtensile bond strength (μTBS) testing after 24 h. The other half was tested after thermocycling (5000 cycles, 5°C-55°C) and storage in water at 37°C for 6 months. Results: One-way ANOVA showed that the number of injections influenced both Rz and RSm roughness parameters (p = 0.00), but not Ra (p = 0.97). One injection exhibited higher (Rz) and grooves with less space between them (RSm) compared to the other groups. For color stability, the values of L*, a*, and b* were influenced by the number of injections (p = 0.00). ΔE = 5 was found for 2 injections and ΔE = 3 for 3 injections, using a control group as reference. One-way ANOVA showed that the number of injections significantly influenced wettability values: 1inj (63 ± 5.3)A > 2inj (49 ± 8.2)B > 3inj (45.8 ± 15.8)B. However, the evaluated factor did not influence the bond strength of non-aged groups. Furthermore, aged groups showed that 1inj (21 ± 37)a presented higher mean values than 2inj (10 ± 8)b or 3inj (12 ± 10.)b. Conclusion: Re-pressing the evaluated ceramic improves roughness and wettability, but compromises the color stability and decreases bond strengths after long-term aging.
Keywords: Ceramic; Leucite-reinforced glass-ceramics; Mechanical properties; Microstructure; Repeated heat-pressing